The Impact of Angry Versus Sad Victim Impact Statements on Mock Jurors' Sentencing Decisions in a Capital Trial. (June 2017) - Nuñez, Narina; Myers, Bryan; Wilkowski, Benjamin M.; Schweitzer, Kimberly
The present study tested the effects of angry and sad victim impact statements (VIS) on jury eligible participants' decisions. Death qualified participants ( N = 581) watched the penalty phase of a capital trial that varied the presence and emotional content of the VIS (angry, sad, or no VIS) along with the strength of mitigating evidence (weak or strong). Results revealed that Angry VIS led to an increase in death sentences, whereas Sad VIS did not. Furthermore, participants who reported becoming angry during the trial were more likely to render a death sentence, but participants who became sad during the trial were not. No interaction was found between VIS and strength of mitigating evidence, but participants exposed to the angry VIS did rate the mitigating evidence as less important to their decisions. The results indicate that VIS are not inherently biasing, nor are all emotions equally impactful on sentencing decisions.